Exploration of Types and Consumption Behaviour of Usada-based Herbal Galactagogue on Lactating Mothers in Bali : Explorasi Jenis dan Perilaku Konsumsi Galaktagogue Herbal berbasis Usada pada Ibu menyusui di Bali - Monika, Ni Luh Gde Mona; Yunita, Ella (Universitas Tadulako, 2021)
Breastfeeding is essential for the health of newborn infants and mothers. Basic health research in 2018 showed that exclusive breastfeeding in Bali has not reached the national target. High rates of cesarean section delay breastfeeding initiation, the important predictor of continued breastfeeding. Main concern for breastfeeding mothers about medications increased the use of herbal galactagogue to aid lactation. The use of traditional medicinal plant in Bali is 40% higher than national average and its existence is strengthened by the issuance of Bali Governor Regulation No. 55/2019 concerning Traditional Balinese Health Services. Despite increasing popularity of traditional medicine, there are currently limited data available on the plant list and pattern of use herbal galactagogue. This study aims to explore the galactagogue plants, pattern of use, perceived effectiveness of herbal galactagogues during breastfeeding among breastfeeding mother’s in Bali. This study was conducted using a questionnaires and in-depth interviews. The questionnaire and interview guideline were validated by lactation consultants and traditional health practitioners in Bali. The study was approved by Human Research Ethic Committee of Bina Usada Bali. The use of herbal galaktagogue is mostly practiced by highly educated mothers, mother’s occupation as health workers and primiparous. There are 26 types of plants that are often used by lactating mothers in Bali. Majority of respondent begin to use herbal galactagogue after giving birth (82%) for approximately less than 1 month. Majority of lactating mothers in Bali perceived effectiveness of herbal galactagogue usage based on breastfeeding adequacy indicators. About 95% respondents feel confidence and have self-empowerment after using herbal galactagogue, possessing psychological benefits. The use of herbal galactagogue is common amongst breastfeeding mothers in Bali, while information about efficacy and safety is lacking. Further research is needed to give evidence-based information to support exclusive breastfeeding